PERSEPSI SISWA TERHADAP KEMAMPUAN MENGAJAR MAHASISWA PPLK DI SEKOLAH LATIHAN PRODI PENDIDIKAN SEJARAH SE-SUMATERA BARAT (SEMESTER GENAP 2013/2014) - MELATI, PUTRI - (Pendidikan Sejarah, 2014)
This study discusses the students perception of the ability to teach students at school PPLK practice throughout the history of the education department of west sumatera (semester 2013/2014),his research . The research problem is how to teach students the ability PPLK to students at the schoolÂ are taught during field prctice education. This study aims to determine the students perception of the ability to teach students the history of education PPLK Prodi in applying (1) Presentation / delivery of learning materials, (2) use of media / learning resources , (3) classroom management , (4) Communication with students,(5) evaluation of learning outcomes. this type of research is a qualitative descriptive study.